Wirausaha Baru Dalam Membangun Fondasi Bisnis - Nico Lukito; Dita Oki Berliyanti; Rowlan Takaya; Vina Ayu Nur Septyana (Politeknik Piksi Ganesha Indonesia, 2025)
Community Service activity was conducted at the Bina Amanah Cordova Entrepreneurship School (SKBAC) Jl. Japos Raya No. 09, Pondok Jati RT 05 RW 03, Jurang Mangu Barat, Pondok Aren, South Tangerang City, Banten Province. The purpose of the activity is to train new entrepreneurs from Micro, Small, and Medium Enterprises (MSMEs) in understanding a strong business foundation as a basis for building and developing sustainable businesses. The problems faced by entrepreneurs, such as a lack of knowledge and skills in designing business models, financial management, marketing strategies, and enhancing entrepreneurial mentality. The training and counseling participants numbered eleven people. The activities included direct mentoring, business simulations, group discussions, and interactive training. The results of the activities show that the participants have a better understanding of basic business concepts and how they can be applied in the businesses they are currently running or will run. This program is expected to help nurture new entrepreneurs who are innovative, resilient, and capable of adapting to market dynamics, as well as contributing to local economic growth.